2012
DOI: 10.4028/www.scientific.net/amr.577.155
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Technique to Control Heat-Damage in Mine

Abstract: With the increasing of exploitation scope and intensity, the deep mining would be the essential choice, where the heat-harm of high temperature becomes one of the main barriers. Through analyzing the thermal damage feature, the cooling technology were be used that put the mine discharge as cold source to control the heat harm. By disposing three main workstation, the technology can be accomplishes its operations and corresponding functions in different exploitation level. Particularly, the exchanged heat sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Studies have indicated that prolonged exposure to high-temperature and high-humidity environments can result in a decline in human physical fitness, making individuals susceptible to heat-related illnesses such as heat stroke, heat halo, central nervous system disorders, and even death. This significantly impacts miners' physical and mental health and jeopardizes the safe and efficient production of mines [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that prolonged exposure to high-temperature and high-humidity environments can result in a decline in human physical fitness, making individuals susceptible to heat-related illnesses such as heat stroke, heat halo, central nervous system disorders, and even death. This significantly impacts miners' physical and mental health and jeopardizes the safe and efficient production of mines [5,6].…”
Section: Introductionmentioning
confidence: 99%